Angelina and the royal wedding - Holabird, Katharine (Holabird, Katharine. Angelina Ballerina., 2022)
Trapped in a castle tower on the morning of Princess Eliza's marriage, bridesmaids Angelina and Princess Sophie hope they will be rescued in time for the wedding processional.